Increased Financial Literacy of Women’s MSMEs Through Sharia Digital Financial Applications - Haryanti, Titik; Sahirin, Rohmat; Wei, Sun (Journal Ligundi of Community Service, 2025)
Background. The limited financial literacy among women-led Micro, Small, and Medium Enterprises (MSMEs) remains a significant barrier to their growth and sustainability, especially in developing countries. Many women entrepreneurs face challenges in managing financial records, accessing funding, and integrating their businesses into formal financial systems. In response, digital financial applications based on Sharia principles have emerged as potential tools to enhance financial literacy and inclusion among Muslim women entrepreneurs. These applications align with religious values and offer features such as transparent transactions, profit-loss sharing models, and zakat tracking. Purpose. This study aims to examine the impact of using Sharia-compliant digital financial applications on the financial literacy of women-led MSMEs. Method. This study uses an adopted qualitative case study approach, which involves in-depth interviews, observations, and document analysis with 15 women entrepreneurs who participated in a financial literacy training program using Sharia digital finance applications (e.g., ShariaBiz or iSaku Syariah). Participants were selected from local MSME networks in West Java, Indonesia. Results. The findings reveal a substantial improvement in the participants’ understanding of basic financial management, including budgeting, saving, debt management, and digital financial transactions. Participants also reported increased confidence in using digital platforms and greater alignment between their financial practices and Islamic values. The Sharia approach contributed to both financial behavior change and ethical business conduct. Conclusion. This study concludes that Sharia-based digital financial tools can serve as effective means of improving financial literacy for women’s MSMEs. These tools also offer a culturally sensitive pathway for promoting inclusive economic development.